C–H Insertion Reactions of Donor/Donor Carbenes: Inception, Investigation, and Insights - Shaw, Jared T. (Synlett, 2020)
Insertion reactions of donor/donor carbenes have emerged from obscurity to become a versatile method for the synthesis of a variety of cyclic structures with excellent control of diastereo- and enantioselectivity. This Account describes the origin of this project as part of a natural product synthesis and the ensuing decade of reaction development that has resulted in new asymmetric methods as well as intriguing tangential observations.
Keywords: C–H insertion; carbenes; rhodium; asymmetric catalysis